Mahovi kot bioindikatorji stanja okolja - Skudnik, Mitja (Gozdarski vestnik, 2011)
As a part of the Intensive Monitoring Programme (IMFE) of Forest Ecosystems inSlovenia, the bryophyte flora and vegetation have been studied. The bioindication role of bryophytes was analyzed on all 11 IM plots. On the selected IM plots (Krucmanove konte, Gorica and Murska šuma) the concentrationof N total and S total were analyzed in living parts of the bryophyte species Hypnum cupressiforme Hedw. The species diversity of bryophytes indicates the site conditions (e.g. bedrock, surface rockiness, soil conditions, micro- and regional climate, vegetation) and forest stand conditions (dominant tree species, dead wood). Analyses of mosses on the selected IMFE plots indicate that the concentration of total nitrogen (N) and sulphur (S) in mosses is the highest on the Murska šuma plot and the lowest onthe Krucmanove konte plot on Pokljuka. Comparing the results with some othercomparable investigations, the Murska šuma plot with its relative high concentrations of total N and S total in moss tissue stands out.
Keywords: natural environment; okolje; bioindikatorji; mahovi; bioindikacija; gozdni ekosistemi